1955
DOI: 10.1121/1.1908155
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Pitch

Abstract: The author, who possesses absolute pitch since the time of his earliest musical experiences at the age of five years, has spent much time in studying this musical phenomenon. Amused by the fact that the most extensive work on “absolute pitch” was conducted by psychologists who did not possess this faculty and that it was done on large groups of students, none of whom possessed this faculty either [For exception see O. Abraham, Sammelbde d. Internat. Musikges 3, 1 (1901) and G. Révész, Zur Grundlegung der Tonps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0
5

Year Published

1975
1975
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 0 publications
3
103
0
5
Order By: Relevance
“…This cannot be explained solely by inheritance, because it is known that the proportion of inherited AP is extremely low. For example, among musicians, the proportion of AP was 8.8% according to Wellek (1963, p. 85) and 3.4% according to Revesz (1913), and among nonmusicians, it was only 0.01 % (Bachem, 1955). The result of an informal test of AP possession for a large number of music students performed on another occasion revealed that no less thanhalf of them were AP possessors.…”
Section: Resultsmentioning
confidence: 99%
“…This cannot be explained solely by inheritance, because it is known that the proportion of inherited AP is extremely low. For example, among musicians, the proportion of AP was 8.8% according to Wellek (1963, p. 85) and 3.4% according to Revesz (1913), and among nonmusicians, it was only 0.01 % (Bachem, 1955). The result of an informal test of AP possession for a large number of music students performed on another occasion revealed that no less thanhalf of them were AP possessors.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, the majority of studies that have investigated functional plasticity have used PET imaging, which requires a relatively large number of subjects per group. To recruit an adequate number of subjects with a specialized skill from within what is already a very small subset of the population would be prohibitve (consider that the prevalence of AP is estimated to be ϳ1/10,000 [2] and the prevalence of early blindness in the United States is probably less than 1/1,000 (see www. cdc.gov/ncbddd/); thus, if they were independent phenomena the overall prevalence would be ϳ1/10,000,000; given the most liberal estimate of dependence (cf.…”
Section: Introductionmentioning
confidence: 99%
“…The lower frequency limit, according to him was impossible to assess due to "disturbing aural and extra aural overtones". Nevertheless, there a "similar fixation of chroma seems to exist" (Bachem, 1955, p. 1182).…”
Section: Frequency Limits Of Absolute Pitch In Previous Studiesmentioning
confidence: 99%
“…At first it must be stated whether we have to deal with a genuine (authentic) absolute pitch or rather with some other, similar phenomenon called pseudo absolute pitch. Such category of non-genuine (non-authentic) absolute pitch was introduced by Bachem (1955) together with a slightly different notion of quasi-absolute pitch. The difference between these two phenomena has been presented not very clearly, so Parncutt and Levitin (2001) in the New Grove Dictionary of Music and Musicians, in place of these two, introduce only one category of non-genuine absolute pitch, namely pseudo absolute pitch.…”
Section: Various Kinds Of Absolute Pitchmentioning
confidence: 99%
See 1 more Smart Citation